Elimination of Citizenship Status for Terrorism Convicts in Indonesia - Abdullah, Gita Septiani (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The revocation of citizenship for terrorism convicts is a complex and controversial issue in Indonesia. The philosophical foundation for this action involves considerations of national security, the protection of human rights, and adherence to the principles of the rule of law. The revocation of citizenship for terrorism convicts is based on the interest of national security. The government believes that by stripping them of their citizenship, they lose access to resources and support that can be used to continue terrorist activities. This step is taken to reduce the threat to national security and society. However, the revocation of citizenship also raises questions regarding human rights. Basic rights of individuals, including the right to citizenship, are guaranteed by various human rights instruments adopted by Indonesia, such as the Universal Declaration of Human Rights and the Human Rights Law. The government's responsibility in protecting the citizenship rights of terrorism convicts encompasses several aspects. First, the government must ensure that the revocation of citizenship is based on valid and convincing evidence and carried out through a fair and transparent legal process. The government should also ensure that terrorism convicts who lose their citizenship still have access to humane treatment and rights guaranteed by international law. They should not become stateless or be deprived of basic rights necessary for a decent life. Overall, the revocation of citizenship for terrorism convicts in Indonesia involves complex considerations between national security and the protection of human rights. The government has a crucial responsibility to maintain a balance between these aspects, ensuring that actions taken are in accordance with the principles of the rule of law and do not violate fundamental rights.